2011
DOI: 10.1118/1.3544353
|View full text |Cite
|
Sign up to set email alerts
|

The impact of anthropometric patient‐phantom matching on organ dose: A hybrid phantom study for fluoroscopy guided interventions

Abstract: Purpose: To investigate the benefits and limitations of patient-phantom matching for determining organ dose during fluoroscopy guided interventions. Methods: In this study, 27 CT datasets representing patients of different sizes and genders were contoured and converted into patient-specific computational models. Each model was matched, based on height and weight, to computational phantoms selected from the UF hybrid patientdependent series. In order to investigate the influence of phantom type on patient organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 18 publications
1
30
1
Order By: Relevance
“…A potential alternative for person‐specific organ dose estimation is to use a library of computational models where habitus‐specific phantoms could serve as alternative models covering various anthropometric and anatomical characteristics of patients . Several habitus‐dependent phantom series have been developed to perform patient‐specific dose estimation by matching anthropometric characteristics of patients, such as gender, age, height, and body weight . Stepusin et al suggested to match patient's data to a computational phantom from a predefined library using height and weight matching for patient‐specific CT dosimetry.…”
Section: Introductionmentioning
confidence: 99%
“…A potential alternative for person‐specific organ dose estimation is to use a library of computational models where habitus‐specific phantoms could serve as alternative models covering various anthropometric and anatomical characteristics of patients . Several habitus‐dependent phantom series have been developed to perform patient‐specific dose estimation by matching anthropometric characteristics of patients, such as gender, age, height, and body weight . Stepusin et al suggested to match patient's data to a computational phantom from a predefined library using height and weight matching for patient‐specific CT dosimetry.…”
Section: Introductionmentioning
confidence: 99%
“…For this study, 52 patient CT image sets were obtained and segmented using 3D‐DOCTOR™ (Able Software Corporation, Lexington, MA, USA). Of these patients, 13 were adult females (previously segmented), 13 were adult males (previously segmented), 13 were pediatric females, and 13 were pediatric males . Eight organs of interest (bladder, heart wall, kidney, liver, lung, pancreas, spleen, and stomach) and homogeneous bone were manually segmented and imported into 3D‐modeling software Rhinoceros™ (Robert McNeel & Associates, Seattle, WA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study by the authors, patientphantom matching was shown effective for increasing the accuracy of organ dose estimation for larger than average patients. 24 Organ size and location, however, played a large role in limiting the effectiveness for smaller than average patients. For skin dose mapping, the primary factor affecting dose is the calculation of the source-to-skin distance.…”
Section: Iic Phantom Selectionmentioning
confidence: 99%
“…The patient-specific phantoms were created previously during the organ dose study by contouring CT datasets retrieved under IRB approval from the PACS system at Shands Jacksonville Medical Center. 24 The major axis represented the patient's lateral width, and the semiminor axis represented the patient's posterior/anterior width as measured for a supine patient. In total, six measurements were needed to create the phantoms and are illustrated in Fig.…”
Section: Iic Phantom Selectionmentioning
confidence: 99%
See 1 more Smart Citation